THE EFFECT OF BALANCED NUTRITION COUNSELING USING ANIMATED VIDEOS ON KNOWLEDGE AND ATTITUDES OF STUDENTS AT PUCANG 1 SIDOARJO - Fersanti, Syafirah Adzraa Nurlail Ananda; Aroni, Hasan; Tapriadi; Riyadi, Bastianus Doddy (Media Gizi Indonesia, 2025)
The lack of knowledge about balanced nutrition is a factor in malnutrition among school-aged children. About 32.3% of elementary school children in East Jawa, Indonesia, experience malnutrition, including those at Pucang 1 Sidoarjo. Efforts to handle this issue can be made through counseling using animated videos. This study aimed to determine the effect of balanced nutrition counseling through an animated video on students' knowledge and attitudes at Pucang 1 Sidoarjo. This study involved 27 fifth-grader respondents who were recruited using a purposive sampling technique. This type of research is pre-experimental with a one-group pretest-posttest design. This study was conducted in August 2023. Data were analyzed using the Paired Sample T-Test and Wilcoxon Rank Test. The counseling significantly affected students’ knowledge (p=0.000) and attitudes (p=0.000).. The average knowledge score of students increased from 59.81±13.48 to 79.63±11.92 after the counseling. The average attitude score of students also increased from 79.66±4.72 to 85.37±7 after the counseling. Counseling on balanced nutrition using animated videos effectively improves the knowledge and attitudes of fifth-grade students at Pucang 1 Sidoarjo.